Simulation of FPGA controlled Single Stage Boost Inverter for the Applications of Grid Connected Photovoltaic System. (December 2017) - Meenakshi Sundaram, B.; Manikandan, B.V.; Kaliamoorthy, M.
Improving the efficiency, reducing the cost and maintaining the power quality of a grid tied with Photovoltaic (PV) system are the important aspects of the present day research. The efficiency of power conversion can be improved by reducing the number of stages. In this paper, a single stage boost inverter topology fed from PV array is used and connected to a single phase grid. Less number of switching components is used in this topology compared to conventional technique and hence, the converter losses are reduced. This can also be very well extended to utility grid system. Further, the proposed topology includes battery backup unit which consists of a DC-DC converter to overcome the variations of Voltage based Maximum Power Point (VMPP) of PV array because of the variations in solar irradiance. The proposed system uses the current control approach which has zero steady state tracking error to control the single stage boost inverter. The proposed system offers many advantages such as low cost, high efficiency, compactness and high quality of output power. Design procedure and simulation results are obtained from MATLAB/SIMULINK and the experimental results are obtained from the model developed in the laboratory. The entire system is controlled by SPATRAN 3A FPGA board.